Lack of panmixia of Bothnian Bay vendace - Implications for fisheries management - López, María-Eugenia; Bergenius Nord, Mikaela; Kaljuste, Olavi; Wennerström, Lovisa; Hekim, Zeynep; Tiainen, Joni; Vasemägi, Anti (Frontiers in Marine Science, 2022)
Overexploitation of fisheries is recognized as a major environmental and socioeconomic problem that threats biodiversity and ecosystem functioning. Inappropriate management policies of fish stocks have been applied as a consequence of inadequate characterization of subtle genetic structure in many fish species. In this study, we aim to assess the extent of genetic differentiation and structure of vendace (Coregonus albula) collected from eight locations in the Bothnian Bay, the northernmost part of the Baltic Sea. Specifically, we test if this species forms a single panmictic population or is divided into several genetically distinct units. We used restriction site-associated DNA sequencing (RAD-seq) to identify 21,792 SNPs based on 266 individuals. We identified a clear pattern of genetic differentiation between River Kalix and the other sampling locations, and a weak structuring between samples from Swedish and Finnish coast. Outlier analysis detected 41 SNPs putatively under divergent selection, mainly reflecting the divergence between River Kalix and the other samples. The outlier SNPs were located within or near 25 genes, including voltage-dependent calcium channel subunit alpha-2 (CACNA2D2), cadherin 26 (CDH26) and carbonic anhydrase 4-like (CA4) that have earlier been associated with salt-tolerance and salinity stress. Our study provides the first genome-wide perspective on genetic structuring of Baltic Sea vendace and rejects the hypothesis of panmixia in the Bothnian Bay. As such, our work demonstrates the power of RAD-sequencing to detect low but significant genetic structuring relevant for fisheries management.